THE ACTION OF REVENGE AS REVEALED BY LORD BLACKWOOD IN SHERLOCK HOLMES THE MOVIE - HARDIANTO, FIKKY (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: safeguarding tendency, neglected style of life, black magic, aggression, accusation Movies cannot be separated from literature. Thus, movies can be analyzed using the theory of literature. Characters in movie can be in the form of human, animals, and others. Every character in movies develops just like in the real life. For example, human characters in movie that also cannot be separated from social life. In the social life, every human had brought social status attached since he/she was born. Social status often creates conflicts in the social life and it develops gradually. The writer conducted the study of the psychological phenomenon that found in one of character in Sherlock Holmes movie. Hence, in this study the writer answered problems of study, namely: (1) What makes Lord Blackwood choose to take revenge in order to safeguard his self-esteem in Sherlock Holmes, the movie (2) How does Lord Blackwood safeguard his self-esteem in Sherlock Holmes, the movie?This study employs qualitative approach to describe the acts of the main character. Descriptive analysis in visual and textual was applied because this study is aimed to comprehend what makes and how the main characters protect his threatened self-esteem.The findings of this study showed that the main character was trying to protect his self-esteem with an uncommon manner. He chose to attack every obstacle that he faced rather than solved it peacefully. To remain in a top of social stratification system, he spread terror through black magic to control the society. In addition, to secure his social status he accused and killed his father who had neglected him. After he got revenge toward his father, he wanted to acquire power in the government to accomplish his superiority complex. However, Sherlock Holmes and his friends had successfully thwarted his efforts.